Effect of carbohydrates on protein hydrolysis in anaerobic digestion - Thu Hang Duong; Miriam van Eekert; Katja Grolle; Thi Viet Nga Tran; Grietje Zeeman; Hardy Temmink (Water Science and Technology, 2022)
This study aimed to assess the effect of carbohydrates on protein hydrolysis and potential implications for the design of anaerobic reactors for treatment of protein-rich wastewaters. Batch experiments were carried out with dissolved starch (Sta) and gelatine (Gel) at different chemical oxygen demand (COD) ratios ranging from 0 to 5.5 under methanogenic conditions for methane production and up to 3.8 under non-methanogenic conditions for volatile fatty acids (VFA), both at 35 °C. The Sta/Gel did not have a direct effect on the gelatine hydrolysis rate constants under methanogenic (0.51 ± 0.05 L g VSS−1 day−1) and non-methanogenic conditions (0.48 ± 0.05 L g VSS−1 day−1). However, under non-methanogenic conditions, gelatine hydrolysis was inhibited by 64% when a spectrum of VFA was added at a VFA/Gel (COD) ratio of 5.9. This was not caused by the ionic strength exerted by VFA but by the VFA itself. These results imply that methanogenesis dictates the reactor design for methane production but hydrolysis does for VFA production from wastewater proteins. HIGHLIGHTS Carbohydrates do not directly affect protein hydrolysis and further degradation.; Methane yield of 82-89% on COD basis when co-digesting proteins and carbohydrates.; Build-up of VFA prevents complete protein hydrolysis in non-methanogenic conditions.; VFA slows down protein hydrolysis rates.;